The Role Of Individualized Instructions - Effect Of Ladder Training Vs Plyometric Training Among Coastal Volleyball Players- A Randomized Trial - R., Priyadharshini; K., Venkatesh; E., Shanmugananth (Journal of Coastal Life Medicine, 2023)
BACKGROUND: Coastal life, because of the abundance of outdoor courts and beach volleyball opportunities, can be a great environment for volleyball players. Millions of people play volleyball in the world. It is considered one of the most competitive sports in many nations. It needs highest level of physical power as well as technical and tactical skills are required. Volleyball is one of the first sports to call on the ability to jump. The jumping force is one of volleyball’s most important characteristics. So using the ladder and plyometric training as a structured individualized instruction technique improves the explosive power of the players was the concept behind AIM: The purpose of this study was to compare the effects of ladder training with plyometric training on volleyball athletes. METHOD: Forty-five male volleyball players between the ages of 19 and 25 were chosen from the coastal area surrounding the Mahatma Gandhi Medical College and Research Institute in Pondicherry. They were designed to participate with inclusion and exclusion criteria. They were divided into three groups at random: Group A (n = 15) received ladder training, Group B (n = 15) received plyometric training, and Group C (n=15) received control training four days a week for six weeks. After 6 weeks of training, the vertical jump test and 3-hop test were evaluated. RESULT: The subjects completed all exams for three groups before and after six weeks of training. Paired t test was used to determine the difference between measurements. One-way ANOVA was performed to determine the difference between groups. Statistically significant difference was found after the 6 weeks of training. There was significantly improvement in both groups (<0.05). CONCLUSION: This study concluded that there was significant improvement in ladder and plyometric training but plyometric training as an individualized instruction technique has better improvement in jump performance.